Sistem Pemerintahan Berbasis Elektronik (SPBE) sebagai Instrumen Inovasi Pemerintah Daerah dalam Menjamin Ketahanan Pangan Berkelanjutan - Komarudin, Dedi; Mu’minah, Sulton; Praja, Selvia Junita; Setiawan, Sigit; Ruhana, Faria (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Food security is not only an agricultural issue, but also closely related to adaptive governance. In the digital era, SPBE is present as a strategic innovation for local governments in ensuring access, distribution and availability of sustainable food. This research uses a descriptive qualitative method with case studies in several regions that have implemented SPBE. The results show that SPBE is able to integrate food data, improve the efficiency of public services, and support national programmes such as Free Nutritious Meals through the involvement of local farmers. The main obstacles include limited digital human resources, infrastructure, and cross-sector coordination. The research recommends strengthening digital institutions, developing regional food dashboards, and increasing digital literacy as strategies to support SPBE-based food security.